Seasonal Changes in Sleep Duration in African American and African College Students Living In Washington, D.C. - Janna Volkov; Kelly J. Rohan; Samina M. Yousufi; Minh-Chau Nguyen; Michael A. Jackson; Courtney M. Thrower; John W. Stiller; Teodor T. Postolache (The Scientific World Journal)
Duration of nocturnal melatonin secretion, a marker of “biological night” that relates to sleep duration, is longer in winter than in summer in patients with seasonal affective disorder (SAD), but not in healthy controls. In this study of African and African American college students, we hypothesized that students who met criteria for winter SAD or subsyndromal SAD (S-SAD) would report sleeping longer in winter than in summer. In addition, based on our previous observation that Africans report more “problems” with change in seasons than African Americans, we expected that the seasonal changes in sleep duration would be greater in African students than in African American students. Based on Seasonal Pattern Assessment Questionnaire (SPAQ) responses, African American and African college students in Washington, D.C. (N = 575) were grouped into a winter SAD/S-SAD group or a no winter diagnosis group, and winter and summer sleep length were determined. We conducted a 2 (season) × 2 (sex) × 2 (ethnicity) × 2 (winter diagnosis group) ANCOVA on reported sleep duration, controlling for age. Contrary to our hypothesis, we found that African and African American students with winter SAD/S-SAD report sleeping longer in the summer than in the winter. No differences in seasonality of sleep were found between African and African American students. Students with winter SAD or S-SAD may need to sacrifice sleep duration in the winter, when their academic functioning/efficiency may be impaired by syndromal or subsyndromal depression, in order to meet seasonally increased academic demands.